2019
DOI: 10.1039/c9gc00387h
|View full text |Cite
|
Sign up to set email alerts
|

Polyhydroxyalkanoate-derived hydrogen-bond donors for the synthesis of new deep eutectic solvents

Abstract: Polyhydroxyalkanoate monomers can serve as deep eutectic solvents components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Thermogravimetric analysis (TGA) was carried out using a Netzsch STA 409 PC Luxx according to protocols described by Haraźna et al [ 42 ] Differential scanning calorimetry (DSC) experiment analyses were performed with a Mettler Toledo 822e calorimeter purged with argon. The samples were first heated from room temperature to 200 °C at 10 K min −1 to erase the thermal history, then the samples were cooled at 10 K min −1 to −80 °C and second heating run at 10 K min −1 were accomplished.…”
Section: Methodsmentioning
confidence: 99%
“…Thermogravimetric analysis (TGA) was carried out using a Netzsch STA 409 PC Luxx according to protocols described by Haraźna et al [ 42 ] Differential scanning calorimetry (DSC) experiment analyses were performed with a Mettler Toledo 822e calorimeter purged with argon. The samples were first heated from room temperature to 200 °C at 10 K min −1 to erase the thermal history, then the samples were cooled at 10 K min −1 to −80 °C and second heating run at 10 K min −1 were accomplished.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, tested acids showed a temperature of melting (T onset ) from 33°C to 66°C and could be applied as PCM in this temperature range. 30 Thermal and chemical stability of pure 3-HFAs were tested using DSC method and 1 H NMR spectroscopy. Considerably lower melting temperatures as well as lower value of the latent heat of melting (ΔH m ) could possibly be due to the presence of 8.5% (w/w) of unsaturated octanoic acid in the sample after described treatment of the polymer, as judged by GCMS analysis.…”
Section: Differential Scanning Analysis Of Pure 3-hfasmentioning
confidence: 99%
“…30 Thermal and chemical stability of pure 3-HFAs were tested using DSC method and 1 H NMR spectroscopy. 30 Small variations in the melting temperature and the change in the latent heat of melting of each of the tested acids were observed, and it can be concluded that they are thermally stable, in cyclic heating and cooling, in the tested temperature range (Figure 2A).…”
Section: Differential Scanning Analysis Of Pure 3-hfasmentioning
confidence: 99%
See 2 more Smart Citations